Reading Between the Lines: How Teachers’ Nonverbal Communication Shapes Learning - Chung, Lauren (Advances in Social Sciences Research Journal, 2025)
This research paper seeks to explore the importance of non-verbal communication, particularly in conveying meaning through facial expressions, eye contact, gestures, and body language, in classroom settings. The paper discusses the three main types of studies: meta-analyses examining the impact of teacher immediacy on student learning; educational dissertations focusing on nonverbal behaviors and academic outcomes; and cross-cultural classroom tests that examine the effects of nonverbal cues during multicultural settings. Ultimately, the paper shows how these nonverbal cues shape student engagement, classroom climate, and more significantly, their academic performance. In addition, the paper considers how students’ nonverbal reactions can offer real-time input that teachers can use to gauge levels of understanding, interest or even confusion. Such feedback is very important to teachers, for it perfectly enables them to adapt in the moment of instruction, by, say, slowing down when learners are lost, offering clarity when things look muddy, and taking things further towards discussion when learners are engaged (Andersen, 1979; Mehrabian, 2009). Responsiveness is not just about making instruction more effective -- it contributes to a class climate where students feel their needs are being taken care of. In contrast, what might be perceived as respectful eye contact, or the expression of a strong and passionate emotion, may be interpreted quite differently in different cultures (McCafferty, 2004; Matsumoto et al., 2013). These misunderstandings can even produce unintentional emotions of alienation in increasingly diverse classroom settings. This paper contends that teachers who are attuned to their own and their students’ nonverbal cues can establish culturally responsive classroom spaces that foster emotional support and increase student engagement by pointing out both the importance of cultural context and the purposeful use of nonverbal communication.